The Use of the Jarimatika Method in Improving Cognitive Development in Early Childhood - Novi Cynthia Yusnita (Jurnal Scientia, 2022)
The process of cognitive development is inseparable from a method or method used by a teacher in providing knowledge to children. This article aims to see how the use of the Jarimatika method in improving the cognitive abilities of Bimbel Calistung Alamanda children. This study uses a descriptive qualitative method that describes the situation that occurs without using calculations. The data collection used is observation, namely by observing children, interviews which are carried out to teachers of the Jarimatika method and documentation, which is carried out to take pictures of some of the children's activities. The subjects of this study were children aged 5-6 years in Bimbel Alamanda. The result of this study is that the use of this Jarimatika method can improve cognitive abilities, especially in the field of arithmetic with three stages, namely (1) the enactive stage, which introduces children to concrete objects around them, (2) the iconic stage, which is manipulating these concrete objects. into a visual form and (3) the symbolic stage in which the child transforms the image into a symbol.